PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN MEDIA EXPOSURE TERHADAP ENVIRONMENTAL DISCLOSURE - Galuh Kirana Nugraheni (2021)
Environmental disclosure is a form of social responsibility disclosure that contains information related to the environment around the company. Disclosure of information and forms of environmental social responsibility, are things that must be done by companies, already regulated in Law no. 40 of 2007 concerning Limited Liability Companies. However, there are still a number of companies that neglect their social environmental responsibility. This study aims to analyze the effect of good corporate governance, company size, and media exposure on environmental disclosure. The method used in this research is quantitative method with hypothesis testing using multiple linear regression assisted by the SPSS 25 application. The data used in this study are secondary data obtained through the official website of the Indonesia Stock Exchange (IDX) for mining sector companies listed in the period 2015-2019, as well as the company's official website. Sampling in this study using purposive sampling method, in order to obtain the sample in this study a number of 12 companies with 5 years running period. The results of this study are the variable size of the audit com-mittee in the company has an influence on environmental disclosure, while for the variable size of the board of commissioners, company size and media exposure have no effect on environmental disclosure.